Gas Release Characteristics in Coal under Different Stresses and Their Impact on Outbursts - Hanpeng Wang (Energies, 2018)
The impact mechanism of in situ stress on outbursts plays a key role in the prevention of outbursts during deep coal mining. The in situ stress may influence the outburst by affecting the gas release intensity according to theoretical analysis, but none of the existing studies have taken into consideration this perspective. To explore whether the influence of in situ stress on gas release in coal is an important reason for stress-induced outbursts, experiments on gas release in coal under different axial stresses and on exposure-induced outbursts with different gases were conducted to respectively study the influence of in situ stress on gas release and the impact of gas release on outburst. The results show that with the increase of stress, the methane release intensity rises by 1~2.4 times and shows an obvious periodicity due to different degrees of fracture development. A small increase in gas release intensity can lead to huge increase in the outburst intensity based on an energy analysis of the outburst experiments, indicating that the gas release intensity is a sensitive physical quantity that influences outbursts. The differences in gas release in coal with different stresses will result in differences in the outburst results based on data from the two experiments, proving that the change in gas release intensity during variations of in situ stress is an important factor for in situ stress-induced outbursts. The research achievements can enrich the impact mechanism of in situ stress on outbursts.